Circular RNAs Could Encode Unique Proteins and Affect Cancer Pathways - Francesca Crudele; Nicoletta Bianchi; Anna Terrazzan; Pietro Ancona; Antonio Frassoldati; Paolo Gasparini; Adamo P. D’Adamo; Dimitrios Papaioannou; Ramiro Garzon; Anna Wójcicka; Paweł Gaj; Krystian Jażdżewski; et al. (Biology, 2023)
circRNAs constitute a novel class of RNA, generally considered as non-coding RNAs; nonetheless, their coding potential has been under scrutiny. In this work, we systematically explored the predicted proteins of more than 160,000 circRNAs detected by exome capture RNA-sequencing and collected in the MiOncoCirc pan-cancer compendium, including normal and cancer samples from different types of tissues. For the functional evaluation, we compared their primary structure and domain composition with those derived from the same linear mRNAs. Among the 4362 circRNAs potentially encoding proteins with a unique primary structure and 1179 encoding proteins with a novel domain composition, 183 were differentially expressed in cancer. In particular, eight were associated with prognosis in acute myeloid leukemia. The functional classification of the dysregulated circRNA-encoded polypeptides showed an enrichment in the heme and cancer signaling, DNA-binding, and phosphorylation processes, and disclosed the roles of some circRNA-based effectors in cancer.